Spitz nevus with EHBP1‐ALK fusion and distinctive membranous localization of ALK. (17th March 2022) - Bahrani, Eman; Kunder, Christian A.; Teng, Joyce M.; Brown, Ryanne A.; Rieger, Kerri E.; Novoa, Roberto A.; Cloutier, Jeffrey M.
Abstract: ALK rearrangements define a histopathologically distinctive yet diverse subset of Spitz tumors characterized by fusiform to epithelioid melanocytes with frequent fascicular growth and ALK overexpression. Molecularly, these tumors are characterized by fusions between ALK and a variety of gene partners, most commonly TPM3 and DCTN1 . We describe an unusual case of a Spitz nevus occurring in a 13‐year‐old female that manifested ALK immunopositivity with cell membrane localization. The proliferation was polypoid and composed of elongated nests of epithelioid melanocytes with enlarged nuclei, prominent nucleoli, and abundant cytoplasm without significant atypia and lacking mitotic figures. The nevus exhibited strong and diffuse expression of p16. Targeted next‐generation RNA sequencing revealed an in‐frame EHBP1 ‐ ALK fusion, which has been reported only once in the literature. EHBP1 encodes an adaptor protein with plasma membrane targeting potential. Together, these findings suggest that the 5′ ALK fusion partner in Spitz tumors may dictate the subcellular localization of the ALK chimeric oncoprotein. In summary, this case highlights a rare ALK fusion associated with a distinct immunohistochemical staining pattern and further expands the spectrum of ALK ‐rearranged melanocytic tumors.